Peningkatan Hasil Belajar Siswa dengan Metode Demonstrasi di Kelas XII MIA 9 SMAN 10 Padang - Rosalina Rosalina (Institut Agama Islam Sumatera Barat, 2022)
This Classroom Action Research aims to improve student learning outcomes by applying the demonstration method to mathematics learning. The research procedure uses Classroom Action Research (CAR) with several cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The research subjects were students of class XII MIA 9 SMAN 10 Padang in the academic year 2018/2019 odd semester as many as 30 people. Data from research results: 33.33% pre-cycle completeness increased in the first cycle completed 63.33%, and increased in the second cycle completed 83.33%. Overall there is always an increase from pre-cycle to cycle II. Thus it can be concluded that: Improving Student Learning Outcomes With the Demonstration Method In Class XII MIA 9 SMAN 10 Padang